KESIAPAN LULUSAN PERGURUAN TINGGI MENETAPKAN AWAL PEMILIHAN KARIER DENGAN MODEL COACHING - T Rony, Zahara (Parameter, 2015)
this research aims to investigate, examine, and develope coaching model to prepare college graduate in determine the first step career choice. This program adopted by company which succeed to improve individual performance. Career coaching program made students ready to face worklife challenges. The data in this research consisted of quantitative data and qualitative data. Quantitative data obtained from the questionnaire structured that assessment used a graduated scale and psychological test for each participants. The questionnaire was distributed to determine the maturity of careers for college graduates of Psychological data can be very important data as the data was used by coach to explore participants potential. As to determine the effectiveness of using qualitative data, researchers conducted observation (field tests) directly, focus group discussion (FGD) and interviews with informants. Based on interviews, observations and field testing of this program has a very decent interpretation of the category. This program can be run by someone who have coaching skills. A high level of competence possessed a coach would greatly affect the successful of this program. At the end of this study will produce a learning model which is "career coaching".